Outcome of neonates with idiopathic respiratory distress syndrome; where do we go wrong? - MBKC Dayasiri; Rajasekara N; Gamage KH; Hemachandra KDHT; Edirisinghe DL (Anuradhapura Clinical Society, 2014)
Background This study focuses on assessing the modifiable risk factors, which are aetiologic in IRDS and the outcome of children who were treated with surfactant therapy. Methods All neonates received by the neonatal intensive care of Anuradhapura teaching hospital with early onset respiratory distress leading to surfactant therapy and among whom chest roentgenograms were supportive of a diagnosis of IRDS, were recruited to study. Appropriate information regarding antenatal and perinatal care, NICU management, complications, and outcomes were collected using a structured questionnaire by the investigators prospectively for one year from January 2012 and retrospectively for the calendar year 2011. Results Seventy one neonates were treated for two year study period and 45(63.4%) were males. Antenatal problems included poor antenatal follow up 5(7%) and bad obstetric history 3(4.2%) with only 52 (73.2%) mothers receiving antenatal steroids. Perinatal problems included eclampsia 8 (11.3%), abruption 5(7%) and fetal distress 2(2.8%) with 23(32.4%) children needing resuscitation at birth. The proportion of pulmonary haemorrhage following surfactant was 14/71(19.7%). Twenty three children (32.4%) were discharged lively and successfully, while 48 children (67.6%) succumbed secondary to extreme prematurity (maturity < 28 weeks) and IRDS 34(70.8%), pulmonary haemorrage 8(17%), septicaemia 8(17%), and severe birth asphyxia 2(4.1%). Conclusion Antenatal glucocorticoids to preterm deliveries, management of maternal medical problems, and control of sepsis in NICU need further improvement to optimize care and to bring down neonatal mortality following IRDS. As pulmonary heamorrhage following surfactant therapy remains a significant factor in increasing neonatal mortality and reducing the weight of the recognized beneficial effects of surfactant, effectiveness of these low cost interventions should be further evaluated.